Immunologically programming the tumor microenvironment induces the pattern recognition receptor NLRC4-dependent antitumor immunity. Issue 1 (19th January 2021) - Yu, Xiaofei; Liu, Wenjie; Chen, Shixian; Cheng, Xueqian; Paez, Patrick A; Sun, Tuanwei; Yuan, Fang; Wei, Chunyan; Landry, Joseph W; Poklepovic, Andrew S; Bear, Harry D; Subjeck, John R; et al.
Abstract : Background: The efficacy of cancer immunotherapy can be limited by the poor immunogenicity of cancer and the immunosuppressive tumor microenvironment (TME). Immunologically programming the TME and creating an immune-inflamed tumor phenotype is critical for improving the immune-responsiveness of cancers. Here, we interrogate the immune modulator Flagrp170, engineered via incorporation of a pathogen-associated molecular pattern (ie, flagellin) into an immunostimulatory chaperone molecule, in transforming poorly immunogenic tumors and establishing a highly immunostimulatory milieu for immune augmentation. Methods: Multiple murine cancer models were used to evaluate the immunostimulatory activity, antitumor potency, and potential side effects of Flagrp170 on administration into the tumors using a replication impaired adenovirus. Antibody neutralization and mice deficient in pattern recognition receptors, that is, toll-like receptor 5 (TLR5) and NOD like receptor (NLR) family caspase activation and recruitment domain (CARD) domain-containing protein 4 (NLRC4), both of which can recognize flagellin, were employed to understand the immunological mechanism of action of the Flagrp170. Results: Intratumoral delivery of mouse or human version of Flagrp170 resulted in robust inhibition of multiple malignancies including head and neck squamous cell carcinoma and breast cancer, without tissue toxicities. This in situ Flagrp170 treatment induced a set of cytokines in the TME known to support Th1/Tc1-dominant antitumor immunity. Additionally, granulocyte macrophage colony-stimulating factor derived from mobilized CD8 + T cells was involved in the therapeutic activity of Flagrp170. We also made a striking finding that NLRC4, not TLR5, is required for Flagrp170-mediated antitumor immune responses. Conclusion: Our results elucidate a novel immune-potentiating activity of Flagrp170 via engaging the innate pattern recognition receptor NLRC4, and support its potential clinical use to reshape cancer immune phenotype for overcoming therapeutic resistance.